The REVITALIZATION of TRADITIONAL ISLAMIC SPIRIT: An Effort to Keep Moderate and Tolerant Religious Model - Amrizal Amrizal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
The implementation of comprehensive democracy after reformation era has created new atmosphere for the reinforcement of absolute puritarinical idea in Indonesian context. Nowadays, the segment of this idea is not only in cultural level but structural level which is systematic and wide. This situation causes the complex religious dynamics in Indonesia.A solution to counterbalance the spread of the “right wing” of Islam which is, to some extent, worrying is to keep moderate and tolerant religious model which could develop the social order of the society which has been harmonious up to now